2020
DOI: 10.1073/pnas.1909172117
|View full text |Cite|
|
Sign up to set email alerts
|

Novel electronic nematicity in heavily hole-doped iron pnictide superconductors

Abstract: Electronic nematicity, a correlated state that spontaneously breaks rotational symmetry, is observed in several layered quantum materials. In contrast to their liquid-crystal counterparts, the nematic director cannot usually point in an arbitrary direction (XY nematics), but is locked by the crystal to discrete directions (Ising nematics), resulting in strongly anisotropic fluctuations above the transition. Here, we report on the observation of nearly isotropic XY-nematic fluctuations, via elastoresistance mea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
49
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 36 publications
7
49
6
Order By: Relevance
“…Very recently, elastoresistance measurements, which can also be used to infer symmetry information on the underlying nematic order parameter, also suggested that a XY‐type of nematic order, that is, a nematic order, which can point in any arbitrary direction, might be realized in a narrow doping window in Ba1xRb x Fe 2 As 2 . [ 243 ] The end members of this series show a nematic ground state with so‐called B2g symmetry and one with B1g symmetry, respectively, and thus the new XY‐type nematic order was proposed to form in between these two extreme limits. From band structure calculations, [ 244 ] it was argued that the change of the nematic order with so‐called B2g symmetry in BaFe 2 As 2 to B1g symmetry in RbFe 2 As 2 is related to the change of the magnetic ground state configuration from single stripe to double stripe.…”
Section: Role Of Uniaxial Pressure For Probing and Tuning Electronic mentioning
confidence: 99%
“…Very recently, elastoresistance measurements, which can also be used to infer symmetry information on the underlying nematic order parameter, also suggested that a XY‐type of nematic order, that is, a nematic order, which can point in any arbitrary direction, might be realized in a narrow doping window in Ba1xRb x Fe 2 As 2 . [ 243 ] The end members of this series show a nematic ground state with so‐called B2g symmetry and one with B1g symmetry, respectively, and thus the new XY‐type nematic order was proposed to form in between these two extreme limits. From band structure calculations, [ 244 ] it was argued that the change of the nematic order with so‐called B2g symmetry in BaFe 2 As 2 to B1g symmetry in RbFe 2 As 2 is related to the change of the magnetic ground state configuration from single stripe to double stripe.…”
Section: Role Of Uniaxial Pressure For Probing and Tuning Electronic mentioning
confidence: 99%
“…However, the nematicity in Fe-based superconductors recently exhibited a very rich variety beyond the original expectation. Well-known discoveries are nematicity without magnetization in FeSe and nematicity with B 2g symmetry in the heavily hole-doped compound AFe 2 As 2 (A = Cs, Rb) [29][30][31][32][33], which is rotated by 45 • with respect to the nematicity in FeSe. These nematic orders are naturally understood as the ferro-orbital and/or bond orders driven by the interference between spin fluctuations described in Fig.…”
mentioning
confidence: 99%
“…6 [41]. Furthermore, elastoresistance measurements in the normal state on this system also revealed a ðπ; πÞ nematicity [44]. ARPES measurements have shown that the Fermi surfaces of the heavily hole-doped FeSCs only have hole pockets centered at the Γ point without electron pockets at the M point [45][46][47].…”
Section: Nematic Superconductivity In 122 Systemmentioning
confidence: 65%